Risk Factors Identification of Fire Incidents in 2017-2018 - Putra Agata Lesmana (The Indonesian Journal of Occupational Safety and Health, 2020)
Introduction: The massive development of the industrial sector leads to an increase in the risk of fire incidents. A company is obligated to prevent, reduce, and extinguish fire incidents by providing training and facilitating supporting tools to avoid fire incidents in the workplace. PT. ARPS is a Surabaya-based manufacturing company that produces plastic packaging and has a potential danger of medium to high levels. By applying the case study design, as an observational study, this study aims to identify the factors that influence and trigger the fire incidents at PT. ARPS during 2017-2018. Methods: The population of this study is the workers of the Assembly Decoration 1 (AD1) and the Blow Molding (DM) production areas. The collected data are analyzed and presented descriptively through tables and narration. Results: The data show that the first fire incident occurred on 10 February 2017 to the KK6 machine in the AD1 area, followed by the second incident that occurred on 18 March 2018 to the VK4 machine in the BM area, and the third incident (30 March 2018) to the KKS6 machine in the AD1 area. Conclusion: It can be stated that the three fire incidents at PT. ARPS that occurred from 2017 until March 2018 are caused by unsafe actions that are the negligence of the human resources, and unsafe conditions, which comprise the unstable machines. Other factors, such as supervision, maintenance, work instruction, and managerial, are identified as the upholding factors to the fire incidents at PR. ARPS. Keywords: factor identification, fire incident, unsafe action, unsafe condition